ФОРМИРОВАНИЕ И УСОВЕРШЕНСТВОВАНИЕ ЦЕННОСТЕЙ У ОБУЧАЮЩИХСЯ В СОВРЕМЕННОСТИ - Рахимов, Б.Х. (SCIENCE and SOCIETY, 2019)
The article deals with the disclosure of some of the goals of modem education. The focus is doneon what are actual today formation in secondary school graduates generalized ways of life, the result of which is not the sum of the assimilation of information, and its ability to operate in a variety of real and problematic situations. It is emphasized that in the professional formation of the future teacher value orientations play a great role.
Keywords: student; future teacher; the value of the system of continuous education; self-regulation; self-awareness; self-knowledge; tolerance